Analysis of ECM performance using critic GRA ‎method - V.P, Ravi; M, Raja; T, Balusamy; P, Anbarasan; R.A, Sankaran (International Journal of Basic and Applied Sciences, 2025)
A hybrid CRITIC-GRA method is adopted to determine the best possible parameter combinations for the ECM drilling process. The input process parameters considered were voltage, duty cycle, and electrolyte concentration. The performance measures ‎considered are machining rate (MR), overcut (OC), and surface corrosion factor (SCF). CRITIC evaluates the standard deviations as 0.33, ‎‎0.29, and 0.29 for MR, OC, and SCF respectively. The weights were calculated as 0.327, 0.238, and 0.435 for MR, OC, and SCF respectively. It ‎was evaluated that voltage at level 3 (9V), duty cycle at level 3 (90%), and electrolyte concentration at level 2 (30gm/l), were the ideal combination for the ECM drilling process. Duty cycle and electrolyte concentration were shown to be the most important parameters influencing ‎quality features based on the ANOVA results. The confirmation results have improved the GRG by 0.1309 from the initial value‎.